Knowledge and attitudes towards Human Papillomavirus infection among staff in a public university in Malaysia - Elbardiny, A. A.; Mohd Zulkefli, Nor Afiah; Md Said, Salmiah (Community Health Society Malaysia, 2014)
Background: Human Papillomavirus (HPV), a sexually transmitted virus, is linked to genital warts and cervical cancer. The aim of this research was to determine the level of knowledge and attitudes regarding HPV and their associated factors among staff in a public university.